Territorial cohesion and regional development in the context of EU integration – the case of Macedonia - Slavica ROCHESKA; Marjan ANGELESKI; Marijana MILEVSKA; Olivera KOSTOSKA (Eastern Journal of European Studies, 2014)
The strategic orientation and candidate status for accession to the European Union clearly point toward the country’s European perspective. In this context, strengthening the territorial cohesion and balanced regional development become crucial for convergence with the EU integration process. Hence, this paper aims at a) disclosing the regional disparities of the country; b) identifying the state of situation in the field of territorial cooperation; c) perceiving potentials for the efficient use of the territorial resource. Secondary data of the last five years, the Official Journal and the Bureau for balanced regional development are used in order to assess the changes in disparity between the eight planning regions in Macedonia while implementing the new policy for balanced regional development. We provide testing for the correlation between the changes in development indices for the two consecutive periods and funds allocated for regional projects during the five-year policy implementation phase.